Critical factor maintenance management for the IBS building in Malaysia / Muhamad Azmi Che Anuar - Che Anuar, Muhamad Azmi (2016)
The main purpose this study to identify the critical factors in implementation effective maintenance management system for IBS building in Malaysia among the Malaysia contractor perception. This study shows the contribution factor that has been contributed to the lack of implementation effective maintenance management for IBS building in Malaysia. To identify the factor by obtaining a feedback have two approach was used which is from the interviews (qualitative) and survey questionnaire (quantitative). Based on literature reviews phase, seven (7) factors was identified as an preliminary contribution factor for critical factor in implementation maintenance management for IBS building as design factor, installation factor, maintenance factor, jointing and connection factor, building quality factor, leakage factor and cost factor. From the first phase of data collection method which is interviews, only three (3) main factor which is design factor, installation factor and maintenance factor found for the further exploration of the problem. Based on two (2) of difference classification contractor which is Grade G6 and G7 contractor were selected to get related additional factor from three main factor. From the interviews finding present that factor related to design factor, knowledge in design, design criteria, design consideration, design conflict and structure analysis that were contributed “critical factor for design factor”. Besides that, factor related to installation factor technique of installation, quality of installation, supervision, contractor attitude and method installation connection were contributed to the “critical factor in installation factor”. Lastly, factor related to maintenance factor, pool of staff with relevant knowledge, maintenance planning, specific tools, and maintenance technologies in market and priority of defect repair. The developed a conceptual framework for hypothesis testing in phase two conducted by the referring on this finding. In the next phase (questionnaire), fifteen (15) variables has identify through interview and it is were tested by using a questionnaire survey form. The factors which is identify as lack knowledge in design, no guidelines in IBS design criteria to follow, lack of design consideration of wet toilet and bathroom, design conflict of IBS component and lack of structure analysis, less of exposure about correct installation technique, less quality work of installation IBS component, lack of supervision during the installation work, attitude among the contractor not prepare correct installation procedure on site and unsuitable method installation use for jointing and connection, hard to pool of maintenance staff with relevant knowledge in maintenance, ineffective maintenance planning, constraint new technologies in market for maintenance management, less specific tools to use in maintenance management and lack of priority of defect repair. According to the mean value in the quantitative result show that ten (10) factor that below 4.50 which is lack of design consideration of wet toilet and bathroom (3.68), Lack of structure analysis (3.00), less of exposure about correct installation technique (3.52), less quality work of installation IBS component (4.32), attitude among the contractor not prepare correct installation procedure on site (3.72), unsuitable method installation use for jointing and connection (3.92), hard to pool of maintenance staff with relevant knowledge in maintenance (3.60), ineffective maintenance planning (4.28), less specific tools to use in maintenance management (3.52) and lack of priority of defect repair (4.44) this factor can be classified not really significant factor. Meanwhile, from the fifteen (15) only five (5) factor were identified as possible critical factor for implementation effective maintenance management for IBS building in Malaysia when the result of mean value is recorded above 4.5. There factor are includes lack knowledge in design (4.56), no guidelines in IBS design criteria to follow (4.56), design conflict of IBS component (4.60), lack of supervision during the installation work (4.76) and constraint new technologies in market for maintenance management (4.56). All of the finding is accepted to help problem that arise for produce effective maintenance management for IBS building in Malaysia.